Feasibility and clinical value of "intelligent" compression and digital storage of transthoracic echocardiograms in day-to-day practice. - Badano, L; Dall'Armellina, E; Bordin, P; Di Chiara, A; Popiel, M; Werren, M; Fioretti, P (2001)
BACKGROUND: The aim of this study was to assess the clinical concordance of expert cardiologists' interpretation of echocardiographic studies recorded on Super-VHS videotape or stored in magneto-optical disk, as well as the feasibility and clinical value of intelligent compression and digital storage of echocardiographic data as cine-loops and still-frames for interpretation of transthoracic echocardiographic images in clinical practice. METHODS: All clinical cardiologists experienced in echocardiography in our department (n = 10) reported on a standardized worksheet checklist the echocardiographic data of 7 consecutive patients (140 reports), and recorded them on videotape or magneto-optical disks to compare the interpretation of videotaped studies, acquired in the usual way, with clinically compressed studies stored to magneto-optical disks using a standard (Italian Society of Echocardiography) image acquisition protocol. RESULTS: The time interval between analog and digital study readings was 50 +/- 15 days. Except for tricuspid valve regurgitation grading (k = 0.28) and for left ventricular global hypokinesia (k = 0.32), the intraobserver agreement in the interpretation of the 3290 cardiovascular morphological and functional findings found on analog and digitally stored images was good (k value ranging from 0.66 to 1.00). The wall motion score index was 1.56 +/- 0.53 when interpreting analog studies, and 1.52 +/- 0.54 on digital studies (p = 0.35). Conversely, the interobserver variability of the wall motion score index (Gini index ranging from 0 to 0.80) was significantly lower when interpreting studies stored digitally than when analog ones were examined (0.48 +/- 0.021 and 0.52 +/- 0.023 respectively, p = 0.006). In comparison to videotape recordings, digital storage of echocardiographic studies significantly shortened the time to image access for study review (327 +/- 62 and 30 +/- 4 s, respectively, p < 0.0001) and the reading time (600 +/- 300 and 540 +/- 300 s respectively, p = 0.034), rendered study accessibility easier (difficult or good: 73 vs 43% of observers, fast or optimal: 27 vs 57% of observers respectively, p = 0.0011) and improved the recorded image quality perception (poor: 25 vs 10% of observers, sufficient or good: 75 vs 90% of observers respectively, p = 0.022), without loss of study completeness (insufficient: 18 vs 17% of observers, adequate or complete: 82 vs 83% of observers, respectively; p = NS). Finally, from September 1, 1999, digital storage has become routine practice for patients admitted to our Department. By December 31, 1999, 411 echo studies had been stored: 7 +/- 3 cine-loop/study, 32 +/- 18 frames/cine-loop, and 3 +/- 2 still-frames/study. The average amount of memory needed for storage was 18.6 +/- 11.9 MB/study. CONCLUSIONS: Clinical compression of echocardiographic studies seems to be an accurate summary of the complete examination recorded to videotape for the assessment of patients admitted in the coronary care unit. In addition, digitally stored studies allow a significant improvement in the interobserver reproducibility of wall motion score assessment.